DETERMINAN KEBIJAKAN HUTANG, DENGAN FREE CASH FLOW SEBAGAI VARIABEL MODERATING, STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA UNTUK TAHUN 2013-2015 - Wasirin, 12.05.52.0111; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of managerial ownership, insider ownership, dividend policy and Investment Opportunity Set (IOS) to debt policy with Free Cash Flow as a moderating variable on manufacturing companies Listed on Indonesia Stock Exchange 2013-2015. The population used in this study are all manufacturing listed on the Indonesia Stock Exchange for the year 2013-2015. This research uses purposive sampling technique in sampling. The analysis was doneÂ by multiple regression using SPSS version 16.00 for windows. The results showed that managerial ownership had positive and insignificant effect on debt policy. The dividend policy has a significant positive effect on debt policy. IOS has a significant positive effect on debt policy. Free cash flow does not moderate the effect of managerial ownership on debt policy. Free cash flow moderates the influence of iOS on debt policy.Keywords:Â Managerial Ownership, Dividend Policy, Investment Opportunity Set, Free Cash Flow and Debt Policy